Haptic Perception of Rod Length When Exploration is Self-Determined, other-Determined, and Self-other Co-Determined. Issue 2 (October 2014) - Park, In-Jo; Rie, Ju-Il
Previous research has shown that when estimating accuracy of an object property like shape, haptic perception is better when exploration is active rather than passive. To further investigate this finding, participants estimated the length of a rod under differing exploration conditions: self-determined, other-determined, and self-other co-determined. During the self-determined exploration, participants moved their end of the rod while the experimenter held the other end of the rod stationary. During the other-determined exploration, the participant held the rod while the experimenter moved the other end. During the self-other co-determined exploration, both the participant and the experimenter moved the rod at the same time. It was hypothesized that judgments of rod length would be significantly more accurate in the self-determined condition than in the other two conditions. Participants were 10 students (6 men, 4 women; M age = 20.6 yr., SD = 1.8) who judged the lengths of five rods (30, 45, 60, 75, and 90 cm long) under the three exploration conditions. For rod length estimation accuracy, self-determined exploration was better than the other-determined or the self-other co-determined exploration. Superiority of self-determined exploration for judging rod lengths has three alternative explanations: (1) anatomical receptors involved in haptic perception, (2) intention to perceive a certain rod property, and (3) need for cognition.